Las redes sociales y su influencia en la relación intrafamiliar de los estudiantes de Bachillerato de la Unidad Educativa “La Providencia”, de la ciudad de Riobamba, periodo Octubre 2012 – Marzo 2013. - Tamayo Orozco, José Esteban (2013)
Recently, online social networks have become very popular and are within the most important sites on the Web. Sites like Facebook and YouTube users averaged 280 million each, with a dizzying growth trend. This research work examined the influence of online social networks in the domestic relations of students in the Providencia Educational Unit, the city of Riobamba as a response from the theory of network analysis for this survey was used as information gathering technique and an instrument the questionnaire, this was applied to the total high school student population. It was evident behavioral patterns of adolescents from online technology as if they have a social network, which is the most widely used network, the time you use them, if affected the family relationship and in which areas. Based on systemic approach explained how the use of online social networks (Facebook, YouTube, Wikipedia, Twitter, MySpace, Sonic and Skype) can modify the structure and family dynamics. What we can say is that online social networks are conditions to be considered as real-world networks with positive and negative effects. Such relationships are impersonal and unreliable